2017
DOI: 10.1111/obr.12589
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of methods to measure family co‐participation in physical activity

Abstract: The family environment is key in influencing children's health behaviours. Encouraging family co-participation in physical activity may therefore be an effective approach to increasing children's physical activity levels. Yet, little is known about how to best assess family co-participation in physical activity. This review summarizes methods to measure family co-participation in physical activity, which was defined as joint physical activities including at least one healthy child (0-18 years) and one other fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 132 publications
0
14
0
Order By: Relevance
“…Being active in PA places may provide better possibilities for children to have unstructured free play that allows them to move around, and therefore is associated with lower ST. Regular co-participation in PA, either inside or outside, benefits the development of children's social, self-regulation and motor skills, but also naturally provides healthy role-modelling opportunities to caregivers [67]. Most of the items included in these visiting PA places variables were activities conducted outside, for instance, in yards, playgrounds and nature.…”
Section: Discussionmentioning
confidence: 99%
“…Being active in PA places may provide better possibilities for children to have unstructured free play that allows them to move around, and therefore is associated with lower ST. Regular co-participation in PA, either inside or outside, benefits the development of children's social, self-regulation and motor skills, but also naturally provides healthy role-modelling opportunities to caregivers [67]. Most of the items included in these visiting PA places variables were activities conducted outside, for instance, in yards, playgrounds and nature.…”
Section: Discussionmentioning
confidence: 99%
“…One parent of the family completed the questionnaire, either in paper- or electronic form. As recommended in a recent review and previously used in this age-group, co-participation in PA was measured by capturing the frequency of co-participation and type of activities completed [ 27 , 43 ]. The type of activities included in the question were purposefully designed for the Finnish context based on our formative work among Finnish parents with preschool-aged children [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that parents play a critical role in developing and shaping the PA and sedentary behavior of their children through role modelling [ 6 , 7 , 8 ]. Previous studies on primary school aged children and their parents have examined the associations between objectively measured PA or sedentary time in parents and their children [ 6 , 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%